PHENex journal - Physical and Health Education Canada. Council of University Professors and Researchers (Acadia University, 2009)
"The first Canadian-based, online, open access, peer-reviewed journal [that focuses] on a broad range of pedagogical, social and cultures issues in physical and health education."
Keywords: Physical education and training : Research : Periodicals; Health education : Research : Periodicals; Éducation physique : Recherche : Périodiques; Éducation sanitaire : Recherche : Périodiques; Health education : Research; Physical education and training : Research